COMPARATIVE ANALYSIS OF THE STUDENT MOVEMENT IN TIANANMEN 1989 AND INDONESIA 1998 ACCORDING TO COMPARATIVE POLITICAL HISTORY IN THE REVIEW OF ISLAMIC VALUES - Mochtar, Moch Galang (Reflektika, 2025)
This article discusses political comparisons of social and political movements in China, namely the Beijing Tiananmen tragedy in 1989 and the May 1998 tragedy in Indonesia. This analysis is seen from aspects of the country’s government system, political and party system, and the implications of the demonstration results. China is a republic with a communist system, while Indonesia is a democracy with a presidential system. These two countries have different political systems, with China using a party political system, namely the Chinese Communist Party, while Indonesia has a multi-party political system. The data used in this research comes from secondary data, specifically through the historical comparison method, which was collected from various previous literature sources, namely websites, historical archives, and research validation journals. This article uses a social and political movement theory perspective. The research results show differences in social and political movements in China and Indonesia, according to the conclusion of the analysis.